Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae) - Skou, Peder; Mironov, Vladimir; Rietz, Hartmut (Zootaxa, 2017)
A new species of the geometrid genus Eupithecia is described from Spain: Eupithecia gypsophilata sp. n. This species belongs to the graphata species group and is somewhat similar externally to Eupithecia gemellata Herrich-Schäffer, 1861.